Employing an active mental task to enhance the performance of auditory attention-based brain–computer interfaces - Xu, Honglai; Zhang, Dan; Ouyang, Minhui; Hong, Bo (Clinical neurophysiology, 2013)
► The active mental task (AMT) generated a stronger late positive ERP response other than the P300 evoked by a traditional oddball counting paradigm. ► The AMT paradigm was explored from its basic neurophysiological characteristics to BCI classification accuracies. ► The results indicate that the AMT paradigm is a candidate for improving the performance of auditory BCIs. A majority of auditory brain–computer interfaces (BCIs) use the attentional modulation of auditory event-related potentials (ERPs) for communication and control. This study investigated whether the performance of an ERP-based auditory BCI can be further improved by increasing the mental efforts associated with the execution of the attention-related task. Subjects mentally selected a target among a random sequence of spoken digits. Upon the detection of the target digit, the subjects were required to perform an active mental task (AMT) – mentally discriminating the gender property of the target voice. The total number of presented digits was manipulated to investigate possible influences of the number of choices. The subjects also participated in two control experiments, in which they were asked to (1) press a button to report their discrimination results or (2) simply count the appearance of the target digit without performing the AMT. Two ERP components, that is, a negative shift around 200ms (Nd) over the fronto-central area and a positive deflection during 500–600ms (late positive component, LPC) over the central–parietal area, were modulated by execution of the AMT. Compared to a counting task, the AMT resulted in paradigm-specific enhanced LPC responses. The latency of the LPC was significantly correlated with the behavioural reaction time, indicating that the LPC could originate from a response-related brain network similar to P3b. The AMT paradigm resulted in an increase of 4–6% in BCI classification accuracies, compared to a counting paradigm that was considered to represent the traditional auditory attention BCI paradigms (p<0.05). In addition, the BCI classification accuracies were not significantly affected by the number of BCI choices in the AMT paradigm. (1) LPC was identified as the AMT-specific ERP component and (2) the performance of auditory BCIs can be improved from the human response side by introducing additional mental efforts when executing attention-related tasks. The neurophysiological characteristics of the recently proposed auditory BCI paradigm using an AMT were explored. The results suggest the proposed paradigm as a candidate for improving the performance of auditory BCIs.